Search for a light pseudoscalar Higgs boson produced in association with bottom quarks in pp collisions at root s=8 TeV - Sirunyan, A. M. (2017)
A search for a light pseudoscalar Higgs boson (A) produced in association with bottom quarks and decaying into a muon pair is reported. The search uses 19.7 fb(-1) of proton-proton collisions at a center-of-mass energy of 8TeV, collected by the CMS experiment. No signal is observed in the dimuon mass range from 25 to 60 GeV. Upper limits on the cross section times branching fraction, sigma(pp -> b $(b) over bar $A) B(A -> mu mu), are set.